2015
DOI: 10.1097/qad.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a social network HIV/STD prevention intervention for MSM in Russia and Hungary

Abstract: Objective To test a novel social network HIV risk reduction intervention for MSM in Russia and Hungary, where same-sex behavior is stigmatized and men may best be reached through their social network connections. Design A 2-arm trial with 18 sociocentric networks of MSM randomized to the social network intervention or standard HIV/STD testing/counseling. Setting St. Petersburg, Russia and Budapest, Hungary. Participants 18 “seeds” from community venues invited the participation of their MSM friends who, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Nevertheless, all patients should be offered information, education and counselling about the risk of reinfection associated with high-risk sexual practices and unsafe drug use [37,155]. Repeated safe sex counselling from health care providers and peers may be considered for HIV-infected MSM with high-risk behaviour [7,[97][98][99][100]. Combined harm reduction interventions should be optimized for all active injectors and HCV care should preferably be integrated in multidisciplinary settings [37,156,157].…”
Section: Addressing Reinfectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, all patients should be offered information, education and counselling about the risk of reinfection associated with high-risk sexual practices and unsafe drug use [37,155]. Repeated safe sex counselling from health care providers and peers may be considered for HIV-infected MSM with high-risk behaviour [7,[97][98][99][100]. Combined harm reduction interventions should be optimized for all active injectors and HCV care should preferably be integrated in multidisciplinary settings [37,156,157].…”
Section: Addressing Reinfectionmentioning
confidence: 97%
“…Repeated risk counselling on HCV transmission before, during, and after HCV treatment might also be beneficial for HCV prevention [7]. A recent randomized trial has shown that a reduction in high-risk sexual practices after a social network intervention led to a decline in the incidence of sexually transmitted diseases/HIV from 15% to 9% [100].…”
Section: Preventionmentioning
confidence: 99%
“…Influencers additionally contribute by being well positioned in social networks to spread behavior change. Interventions that operate through social networks hold promise for reaching vulnerable communities, particularly when formal prevention infrastructure supports are limited [17,47]. 375 376 377 378 379 380 381 382 383 384 385 386 387 388 389 390 391 392 393 394 395 396 397 398 399 400 401 402 403 404 405 406 407 408 409 410 411 412 413 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 442 443 444 445 446 447 448 449 450 451 452 453 …”
Section: Discussionmentioning
confidence: 99%
“…Two surveillance studies among MSM in Moscow and St. Petersburg showed 6% HIV prevalence. [5,6] However, the true prevalence may be higher. A recent large, respondent-driven sample of over 1,300 MSM in Moscow showed biologically-identified HIV prevalence of up to 15.6% (with a population level estimate of 11.6%).…”
mentioning
confidence: 99%